2021
DOI: 10.1101/2021.03.18.435634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assigning confidence to structural annotations from mass spectra with COSMIC

Abstract: Untargeted metabolomics experiments rely on spectral libraries for structure annotation, but these libraries are vastly incomplete; in silico methods search in structure databases but cannot distinguish between correct and incorrect annotations. As biological interpretation relies on accurate structure annotations, the ability to assign confidence to such annotations is a key outstanding problem. We introduce the COSMIC workflow that combines structure database generation, in silico annotation, and a confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Recently, we reported that gut microbes in humans and mice can also conjugate cholic acid with Leu, Phe, and Tyr 33 . Since then, we have also found Ser conjugated to cholic acid, Phe conjugated to deoxycholate 19 and in silico predictions for twelve bile acids conjugates where Phe and Trp chenodeoxycholic acid conjugates were validated 34 . Following these discoveries, we imagined that these microbially conjugated bile acids were part of a much larger class of bile acid amidates that includes other naturally occurring amino acids, both proteinogenic and non proteinogenic.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, we reported that gut microbes in humans and mice can also conjugate cholic acid with Leu, Phe, and Tyr 33 . Since then, we have also found Ser conjugated to cholic acid, Phe conjugated to deoxycholate 19 and in silico predictions for twelve bile acids conjugates where Phe and Trp chenodeoxycholic acid conjugates were validated 34 . Following these discoveries, we imagined that these microbially conjugated bile acids were part of a much larger class of bile acid amidates that includes other naturally occurring amino acids, both proteinogenic and non proteinogenic.…”
Section: Introductionmentioning
confidence: 90%
“…The authors have previously demonstrated that taxonomically informed metabolite annotation is critical for the improvement of the NP annotation process ( Rutz et al, 2019 ). Alternative approaches linking structural annotation to biological organisms have also shown substantial improvements ( Hoffmann et al, 2021 ). In this context, the LOTUS initiative offers new opportunities for linking chemical objects to both their biological occurrences and spectral information and should significantly facilitate such applications.…”
Section: Resultsmentioning
confidence: 99%
“…19 However, NMR delivers highly specific structural information and direct quantification capabilities. 1,20 Even though, most studies dealing with complex mixtures and NPs tend to prefer the use of MS-based techniques, the compound annotation capability of MS is intrinsically limited to molecular weight and other general structure information 21 ; e.g. it is generally impossible to assert the position of substituents.…”
Section: Resultsmentioning
confidence: 99%